Critical flux behavior in pressure-driven and osmotic-pressure-driven membrane processes - Zou, Shan (2014)
Among the numerous topics related to membrane separation processes, flux performance study remains as the core and foundation of academic research as well as practical application. The current study focuses on the critical flux phenomena in pressure-driven (microfiltration (MF)) as well as in osmotically-driven membrane processes (forward osmosis (FO)). For the MF system, two MF membranes (pore size of 0.1 µm and 0.2µm, respectively) were applied to filter mixed liquor from conventional activated sludge as well as that from a membrane bioreactor (MBR). The critical flux behavior was studied by “pressure stepping “method and “pressure cycling” method under different test conditions. It was found that critical flux evaluation protocol could significantly affect the critical flux value, e.g., lower values were obtained for longer time interval used for the pressure stepping. For the FO process for microalgae harvesting, the algae species Chlorella Sorokiniana was used in the feedwater in a cross flow mode FO system. The effect of physical parameters (flux level, membrane orientation, and cross flow) on FO fouling and flux behavior during algae separation were investigated. The impact of chemical parameters (feed water chemistry, draw solution chemistry) was explored by adding Mg2+ ions into the feed water and draw solution. The concept of critical flux was applied successfully in FO process. Moreover, a systematic study to investigate the effect of solute back diffusion, a unique phenomenon in FO process, on FO fouling revealed that the critical flux can be drastically reduced as a result of the specific foulant-ion interaction induced by the diffusion of Mg2+ from the draw solution to the feed solution. Depends on the semi-transparency feature of the flat-sheet FO membrane and the good visibility of algae cells through microscope, direct observation method was further applied to monitor algae deposition on FO membranes. Microscopic images were analyzed and characterized to show the process of fouling under various solution chemistry and operational conditions. The microscopic results were further compared to the flux behaviour to evaluate its potential as a critical flux determination method.